Understanding Weber [ - Whimster, Sam , 1947- (London ;New York : Routledge, 2007)
A companion to "The Essential Weber", this work explains the central issues of Weber's work. It locates the central issues in Weber's writings and relates them to the golden era of social and cultural
Weber before Weberian sociology, revisited -- Capitalism in contemporary debates : Sombart, Weber and Simmel -- The Protestant ethic and the "spirit" of capitalism -- 'Wissenschaftslehre' -- The reluctant sociologist : from the Protestant ethic to the Grundriss der Sozialokonomik --The sociology of religion --
Going beyond Weber --Power, legitimacy, and democracy --Sociological categories and the types of economic activity : a final account
Description based on print version record
Includes bibliographical references and index
Keywords: Weber, Max , -- 1864-1920 -- Criticism and interpretation; Economics; Religion and sociology; Sociology